Description vs deforestation: Couepia brevistaminea (Chrysobalanaceae), a new species on the frontier of agricultural expansion in the Brazilian savanna - Barbosa-Silva, Rafael Gomes; Antar, Guilherme Medeiros (Phytotaxa, 2020)
The Brazilian savanna (Cerrado domain), although without significant richness of Chrysobalanaceae, has widely distributed species of this family, and some endemic to this domain. Couepia, a Neotropical genus, includes 62 species distributed mainly in lowland tropical forests with three species recognized for the Brazilian savanna. Here we report a new species of Couepia endemic to Brazilian savanna in the region with the greatest agricultural advance in Brazil, from the states of Tocantins and Goiás. We provide a description, a distribution map, photographs, a preliminary conservation status assessment and comparisons with other species of the genus that occur in this domain. With this addition we help to contribute to the knowledge of plant biodiversity, which is an urgent and fundamental step towards planning and carrying out conservation actions.